2019
DOI: 10.1159/000501722
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Prevalence of Overweight and Obesity among Children Aged 2–7 Years from 2011 to 2017 in Xiamen, China

Abstract: <b><i>Background:</i></b> Childhood overweight and obesity have become some of the most serious public health problems in the 21st century and have a significant impact on affected children as they grow into adulthood. <b><i>Objective:</i></b> The purpose of this study was to evaluate the overweight and obesity status and their main influencing factors in preschool children aged 2–7 years in urban areas of China between 2011 and 2017. <b><i>Methods:&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Xiamen, China. The prevalence of severe obesity decreased from 0.32% in 2011 to 0.28% in 2017 in preschool children aged 2–7 years ( n = 567,338) in urban areas [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiamen, China. The prevalence of severe obesity decreased from 0.32% in 2011 to 0.28% in 2017 in preschool children aged 2–7 years ( n = 567,338) in urban areas [36].…”
Section: Resultsmentioning
confidence: 99%
“…Xiamen, China. The prevalence of severe obesity decreased from 0.32% in 2011 to 0.28% in 2017 in preschool children aged 2-7 years (n = 567,338) in urban areas [36]. Korea Data from 19,593 youth (10,271 boys) aged 2-19 were obtained from the Korean National Health and Nutrition Examination Surveys (2001-2014) [9].…”
Section: Severe Childhood Obesity According To Region Us -Nhanes Reportsmentioning
confidence: 99%
“…About 11% of the children were underweight. Chen et al [25] reported that in preschoolers aged 2 to 7 years, the prevalence of overweight and obesity was 10.91 and 5.66%, respectively. In the same line, in the study by Al-Taiar et al [26] of the 5119 children, 163 (3.18%) and 332 (6.48%) were obese or overweight children.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [25] reported that Obesity in preschoolers is associated with birth weight and infant eating practises. Infant formula feeding and early introduction of solid meals are significant contributors to childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…To cross-validate our results, we also employ the WHO growth chart (Onis et al, 2007) to show that our results are robust. The WHO measure is an international standard that has been widely used to measure children's weight in China (e.g., Chen et al, 2019;Dong et al, 2018;Kong et al, 2019;Wu, 2006). An advantage of the WHO measure is that it not only provides the overweight thresholds, but also how much overweight above the thresholds.…”
Section: Alternative Measurementioning
confidence: 99%